Strengthening Audit Quality through Ethics and Skepticism: Evidence from Internal Auditors in Timor-Leste - Dewi Diah Fakhriyyah; M. Cholid Mawardi; Lidia Tilman Dos Santos (Golden Ratio of Auditing Research, 2026)
High-quality audits are increasingly needed to support transparency and accountability in government financial governance, including in Timor-Leste, a developing country. This study examines the influence of professional ethics and professional skepticism on auditor quality and investigates the moderating role of professional skepticism. The population consists of all government internal auditors at the Inspeção Geral do Estado (IGE), and a saturated sampling technique was employed, using the entire population as the sample. A quantitative method was adopted, with data evaluated using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings are professional ethics can enhance auditor quality, professional skepticism also enhance auditor quality, demonstrating that a critical and questioning perspective improves the trustworthiness of audit outputs. Furthermore, professional skepticism enhance the effect of professional ethics on auditor quality. These findings provide theoretical implications by supporting agency theory, where auditors play a essential role in reducing information asymmetry between principals and agents, and attribution theory, where auditors’ skeptical judgment reflects cognitive processes in evaluating and attributing the credibility of audit evidence. Overall, the integration of professional ethics and professional skepticism is essential to improvi the quality of government internal auditors, thereby supporting more transparent and accountable public financial governance in Timor-Leste.